Pengaruh Kinerja Perusahaan Dan Laverage Terhadap Manajemen Laba Di Bank Umum Syariah Indonesia - Iqbal Firmani; Slamet Haryono (STIE PGRI Dewantara Jombang, 2021)
This study aims to analyze earning management in sharia commercial banks in Indonesia (priode 2015-2019), while the method of earningt management analysis used is Modified Jones Model. Through Random Sampling technique, 8 sharia commercial banks (BUS) are used as sempel, the banks are: BNI Syariah, BRI Syariah, Mandiri Syariah, BCA Syariah, BTPN Syariah, Bank Muamalat, Bank Mega Syariah and Bank Syariah Bukopin. The results of the Modified Jones Model profit management account show that the majority of Sharia commercial banks tend to make profit management by reducing the value of their profits. Through the regression panel data conducted analysis of the influence of company performance and leverage on profit management, regression results through t-tests showed that the company's performance and laverage did not have a significant influence on earning management.